ANALISIS PEMBERIAN KREDIT MOTOR PADA PT BFI FINANCE INDONESIA Tbk BANJARMASIN - Mohdari Mohdari; Masrifani Masrifani; Ahmad Tijani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Banks are not able to accommodate the credit needs of the community, so that non-bank financial institutions offer credit solutions. The problem faced by financial institutions is bad credit. This study aims to look at the analysis of lending carried out at BFI Finance Indonesia, Tbk, especially at the Banjarmasin branch in order to minimize the risk of bad loans. This research is a descriptive quantitative research conducted by distributing questionnaires to selected customers. The results of the study show that the procedure for providing credit in the company is still weak, namely in the survey and analysis section it is carried out by one Account Executive (AE), this can cause bad loans every month. There is no separation of duties in the Account Executive (AE) section, Account Executives (AE) can work simultaneously without having each responsibility.